Synthesis of α-Keto Amides by a Pyrrolidine/TEMPO-Mediated Oxidation of α-Keto Amines - Yu, Lu; Somfai, Peter (Synlett, 2016)
A mild procedure has been developed for the synthesis of α-keto amides by α-oxidation of the corresponding α-keto amines mediated by pyrrolidine and TEMPO. The method can also be applied to the synthesis of α-keto thioamides and α-keto amidines.
Keywords: oxidation; catalysis; amides; ketones; amines; thioamides